(untitled) (Sains Humanika, 2011)
This article aims to analyze the development of Islamic Stock Market (ISM) in Malaysia from 1999 until 2009. ISM is one of the prominent components in Malaysian Stock Exchange E_ìêë =j ä óëá F. It refers to the sale and purchase transaction of stock that has Shariah complaint company activities and transacted in Malaysian Exchange. Due to this reason, Shariah Advisory Committee of Security Commission has established a list of Shariah compliant counters by basing on the main references (al-Quran and al-Hadith), other advocating sources and consensus research method that lead investors to participate in the field of Islamic investment without hesitation. As a result, Shariah compliant counters majored the overall number of counters in Malaysian Stock Exchange beyond 88% with capital market value of 63.8% from the overall capital market in Malaysia in 2009.